Perceived Self-Efficacy and Its Relationship with Psychological Resilience among Track and Field Athletes - Ahmed, Rasha Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Psychological factors play a central role in athletic performance, particularly in individual sports requiring high personal responsibility. Specific Background: Perceived self-efficacy and psychological resilience are considered core constructs in sport psychology, yet empirical examination among track and field athletes in Iraq remains limited. Knowledge Gap: Few studies have constructed validated measurement tools tailored to this population while simultaneously examining the predictive relationship between these two psychological variables. Aims: This study aimed to develop and validate scales for perceived self-efficacy and psychological resilience and to examine their correlational and predictive relationship among Iraqi Athletics League athletes (2023–2024). Results: Findings revealed high levels of perceived self-efficacy (M = 136.312) and psychological resilience (M = 173.517), with a significant positive correlation (r = 0.661, p < 0.05). Regression analysis indicated that psychological resilience significantly predicts perceived self-efficacy (Self-Efficacy = 17.526 + 0.232 × Resilience). Novelty: The study provides newly validated sport-specific scales and empirical evidence of a predictive psychological model in track and field athletes. Implications: Integrating structured psychological preparation programs into athletic training is recommended to support performance stability and competitive readiness. Highlights: High levels of self-efficacy and resilience were identified among athletes. A strong positive correlation (r = 0.661) was confirmed. Psychological resilience significantly predicts perceived self-efficacy. Keywords: Perceived Self-Efficacy; Psychological Resilience; Track and Field; Sport Psychology; Regression Analysis